COMPARATIVE STUDY OF CHOLESTEROL ALTERATIONS IN A FRESHWATER TELEOST FISH, AMBLYPHARYNGODON MOLA EXPOSURE TO HEAVY METALS - D. SHELKE ABHAY (The Bioscan, 2013)
Effect of mercuric chloride, arsenic trioxide & cadmium chloride on total cholesterol alteration in liver and gonads of a freshwater teleost fish, Amblypharyngodon mola were studied. The fishes were exposed to 0.2291 ppm. mercuric chloride, 1.4557 ppm. Arsenic trioxide and 3.1395 ppm. Cadmium chloride as a chronic treatment. In experimental groups a progressive decrease in total cholesterol content were found with respect to exposure period in liver and gonads after chronic exposure to Mercuric chloride, Arsenic trioxide and Cadmium chloride as compared to control groups.